Indian Contribution to Language Sciences in Non-Western Tradition: With Reference to Arabic - Rangkuti, Rahmadsyah; Hasnain, S. Imtiaz (Talenta Publisher, 2018)
Language study relates itself to both ontology and epistemology. Both ontological and epistemological investigations have been the subject of debate and discussion in different civilizations producing a number of grammatical traditions other than the West. Arab, China, India and the ancient Near East can also boast of language traditions of greater antiquity. In terms of richness of insight and comprehensiveness of scope, both India and the Arab compete on equal terms with the West, where each grew independently of the others and for the most part developed separately, drawing on the resources of the culture within which it grew. Hence, there is strong need to have a study of comparative grammatical theory to which Indian, Arabs and Chinese also belong, centring on the questions of: What has been the importance of these theories explanatory categories appear in historically unrelated linguistic theory, and if they do, why? This perspective would bring new dimension to the study of linguistic theory and would not remain at the level of redressing the overwhelming emphasis on the European tradition in the study of history of linguistics.